Iron- and Hepcidin-Independent Downregulation of the Iron Exporter Ferroportin in Macrophages during Salmonella Infection - Willemetz, Alexandra; Beatty, Sean; Richer, Etienne; Rubio, Aude; Auriac, Anne; Milkereit, Ruth J.; Thibaudeau, Olivier; Vaulont, Sophie; Malo, Danielle; Canonne-Hergaux, François (Frontiers in Immunology, 2017)
Retention of iron in tissues macrophages via upregulation of hepcidin (HAMP) and downregulation of the iron exporter ferroportin (FPN) is thought to participate in the establishment of anemia of inflammation after infection. However, an upregulation of FPN has been proposed to limit macrophages iron access to intracellular pathogens. We therefore studied the iron homeostasis and in particular the regulation of FPN after infection with Salmonella enterica serovar Typhimurium in mice presenting tissue macrophages with high iron (AcB61), basal iron (A/J and wildtype mice), or low iron (Hamp knock out, Hamp-/-) levels. The presence of iron in AcB61 macrophages due to extravascular hemolysis and strong erythrophagocytosis activity favored the proliferation of Salmonella in spleen and liver with a concomitant decrease of FPN protein expression. Despite systemic iron overload, no or slight increase in Salmonella burden was observed in Hamp-/ mice compared to controls. Importantly, FPN expression at both mRNA and protein levels was strongly decreased during Salmonella infection in Hamp-/- mice. The repression of Fpn mRNA was also observed in Salmonella infected cultured macrophages. In addition, the downregulation of FPN was associated with decreased iron stores in both liver and spleen in infected mice. Our findings show, that during Salmonella infection FPN is repressed through an iron and hepcidin independent mechanism. Such regulation likely provide the cellular iron indispensable for the growth of Salmonella inside the macrophages.